2023
DOI: 10.3390/su152115569
|View full text |Cite
|
Sign up to set email alerts
|

Responses of In Vitro Strawberry Plants to Drought Stress under the Influence of Nano-Silicon Dioxide

Sevinç Şener,
Hülya Sayğı,
Canan Nilay Duran

Abstract: The aim of the study is to determine the effectiveness of nano-silicon dioxide (NaSiO2) application on the tolerance of strawberry plants exposed to drought stress under in vitro conditions. Drought stress was induced with polyethylene glycol (PEG-6000). In the experiment, the effects of PEG 6000 concentrations (0, 4, 8%) and NaSiO2 concentrations (0, 50, 100 mg L−1) on in vitro strawberry plants were determined. Plants treated with PEG 6000 showed reduced vegetative growth parameters, but this decrease was re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…The increase in root count at the maximum PEG concentration for all cultivars is reminiscent of the findings of Zahedi et al [53], in whose study the accumulation of osmolytes and enhanced antioxidant enzyme activities were observed under severe drought stress. The decrease in root length at 6 mg/L PEG corresponds to Şener et al [51], in whose study nano-silicon dioxide application mitigated reduced vegetative growth under drought stress. Our data on root rates at different PEG concentrations align with a study by Josefi et al [52], emphasizing the influence of jasmonic acid (JA) on morphophysiological and biochemical characteristics under PEG-induced water stress.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The increase in root count at the maximum PEG concentration for all cultivars is reminiscent of the findings of Zahedi et al [53], in whose study the accumulation of osmolytes and enhanced antioxidant enzyme activities were observed under severe drought stress. The decrease in root length at 6 mg/L PEG corresponds to Şener et al [51], in whose study nano-silicon dioxide application mitigated reduced vegetative growth under drought stress. Our data on root rates at different PEG concentrations align with a study by Josefi et al [52], emphasizing the influence of jasmonic acid (JA) on morphophysiological and biochemical characteristics under PEG-induced water stress.…”
Section: Discussionsupporting
confidence: 59%
“…Our experimental results reveal significant insights into the responses of three strawberry genotypes ("Festival", "Fortuna", and "Rubygem") to varying concentrations of polyethylene glycol (PEG) simulating drought stress. In comparing our findings with studies by Hussein et al [49], Mozafari et al [50], Şener et al [51], Josefi et al [52], and Zahedi et al [53], we can draw valuable comparisons to elucidate the implications of our results. The results indicate that PEG concentrations influence plant height, with the "Fortuna" cultivar reaching its maximum height in a PEG-free medium, while "Festival" showed the shortest height at 6 mg/L PEG.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation